Validation of an indirect data collection method to assess airport pavement condition - Santos, Bertha (2020)
The authors acknowledge University of Beira Interior, CERIS - Civil Engineering Research and Innovation for Sustainability (ECI/04625), GEOBIOTEC - GeoBioSciences, GeoTechnologies and GeoEngineering (GEO/04035) and ASA SA, Cape Verde Airports and Air Safety for support and funding of this study.